2015
DOI: 10.4103/2249-4863.152236
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of teaching and learning in family medicine by students: A Sri Lankan experience

Abstract: Background:Family Medicine occupies a prominent place in the undergraduate curriculum of the Faculty of Medicine, University of Kelaniya, Sri Lanka. The one month clinical attachment during the fourth year utilizes a variety of teaching methods. This study evaluates teaching learning methods and learning environment of this attachment.Methodology:A descriptive cross sectional study was carried out among consenting students over a period of six months on completion of the clinical attachment using a pretested s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…These findings are in agreement with those of Ramanayake et al 5 , in Sri Lanka, who found that that the vast majority (92%) of family medicine candidates appreciated its environment and teaching methods.…”
Section: Discusson:-supporting
confidence: 92%
“…These findings are in agreement with those of Ramanayake et al 5 , in Sri Lanka, who found that that the vast majority (92%) of family medicine candidates appreciated its environment and teaching methods.…”
Section: Discusson:-supporting
confidence: 92%
“…They also serve as integral, complementary members of primary health care team, providing supervision for other health workers and ensuring comprehensiveness, continuous, and coordinated health care for individuals, families, and communities. [ 13 ] The recently formulated draft for national health policy has emphasized the importance of promoting family medicine training in the country to strengthen primary care workforce, and thus reduce the unmet needs of specialist services. [ 12 ] Our landscaping of family medicine courses has revealed three major findings which are critical: Lack of mainstreaming of family medicine teaching in undergraduate medical and nursing education, nonexistence of family medicine specialty, and limited scope for capacity building with paucity of accredited courses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] In Sri Lanka and South Africa, similar initiatives have shown encouraging results. [ 11 13 ] Contrastingly, in India, there is a void of family medicine in current undergraduate medical education. It is well evident that future health care professionals will need strong skills in the fundamental aspects of family medicine to gain confidence and expertise in dealing with complex physical, psychological, and social problems, as first contact physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was administered to six consecutive clinical groups at the end of the 1 month clinical appointment. This survey showed that direct observation of student consultations and feedback from teachers was the most popular teaching method among students while need to strengthen hands on learning methods such procedural skills and clinical examination techniques was emphasised [8].…”
Section: Introductionmentioning
confidence: 99%